2016
DOI: 10.1109/tmag.2016.2517600
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Interfacial Anisotropies of Pt/Co/AlOxPerpendicularly Magnetized Thin Films

Abstract: Thin films of Pt/Co/AlO x , showing perpendicular magnetic anisotropy, were grown by magnetron sputtering with the AlO x formed by oxidation of thin Al layers using an oxygen atom source. Films were studied as a function of Pt thickness and Al oxidation and films which showed full remanence and sharp switching coercive were achieved. In order to prevent further oxidation of the interface in ambient conditions we use a double Al growth and oxidation process. Magneto optical Kerr effect and vibrating sample magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…, (5) where ς = ωt, T = (βJ 1 ) −1 , h = H 0 /J 1 , d A = D A /J 1 and Ω = τ ω, z = 4 and ω = 2πv are taken. The mean-field dynamical equation for the average magnetizations of m 1 B , m 2 A , and m 2 B can be similarly obtained as…”
Section: Model and Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…, (5) where ς = ωt, T = (βJ 1 ) −1 , h = H 0 /J 1 , d A = D A /J 1 and Ω = τ ω, z = 4 and ω = 2πv are taken. The mean-field dynamical equation for the average magnetizations of m 1 B , m 2 A , and m 2 B can be similarly obtained as…”
Section: Model and Formulationmentioning
confidence: 99%
“…(see Refs. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and references there in). Theoretically, the spin-1/2 (see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Between these two interfaces, Mansell et al demonstrated that the bottom Pt=Co interface, where Co is hybridized with Pt (an element showing a strong SOC), has the highest contribution to the PMA. 11) On the other hand, Manchon et al gave more emphasis to the top Co=MO x interface, where the charge transfer between Co and oxygen induces a strong PMA. 6,7) However, in the absence of a quantitative analysis on the individual PMA strengths at the two interfaces of Pt=Co and Co=MO x , it is not possible to predict which interface gives the dominant contribution to the total PMA.…”
mentioning
confidence: 99%